Enhancement of Organics Removal by an Integrated Nonwoven Media Biofilter–submerged Membrane Adsorption Hybrid System - Guo, W. S.; Xing, W.; Ngo, H. H.; Hu, A. Y. J.; Palmer, C. G.; Zhang, R. (Journal of Applied Membrane Science & Technology, 2017)
This study aims to investigate the feasibility of using nonwoven fabric material (NB) as bedding material in a circulating fluidized bed biofilter (FBB), coupling with a submerged membrane adsorption hybrid system (SMAHS) to treat high strength synthetic wastewater containing refractory organic pollutants. The results show that the NBFBB could remove major part of the organic pollutants at relatively low influent feeding rate of 10 and 20 mL/min with the bed depth of 25 cm and minimum recirculation rate of 50%. The integrated NB–FBB–SMAHS system exhibited excellent DOC and nutrient removal with the bed depth of 45 cm and 50% recirculation rate. At the NBFBB influent feeding rate of 50 mL/min, the system removed more than 96% of DOC, 100% of NH4–N and 84.2% PO4–P with a low TMP development of 9.5 kPa. Molecular weight (MW) distributions also indicated that the system could eliminate dissolved organic pollutants range from 90 to 40200 Daltons.